Strategi Orang Tua Dalam Mengajarkan Pendidikan Agama Kristen Kepada Anak di Keluarga Berdasarkan Efesus 6:4 - Marianus -; Talizaro Tafonao; Agiana Her Visnhu Ditakristi; Manahan Uji Simanjuntak; Daniel Agustin (APOSTOLOS, 2022)
The purpose of writing this article is to see the impact of teaching Christian religious education to children in the family based on Ephesians 6:4. The main issue that often occurs in the family so far is that parents (fathers) are not good teachers and role models for children, and not even a few children are hurt mentally just because of their parents' actions. The main issue that often occurs in the family so far is that parents (fathers) are not good teachers and role models for children, and not even a few children are hurt mentally just because of their parents' actions. The method used in this study is a descriptive qualitative research method. The results obtained in this paper are that educating children with love according to God's teachings and advice is an urgent matter in the family. Thus, education in the family has a very significant role in shaping every child and this cannot be ignored by every parent.